A SYSTEMATIC REVIEW OF RISK MANAGEMENT AND SUSTAINABILITY ISSUE: FUTURE RESEARCH RECOMMENDATION - Nur, Siti; Subastyan, Galih Mulya (Journal of Applied Accounting and Taxation, 2026)
The development of risk management can be observed from the increasing number of studies published each year. In response to this development, a literature review has been conducted to provide guidance for the evolution of risk management research. Therefore, the aim of this study is to highlight the main findings from research on risk management. This study utilizes 26 previous studies published in the Scopus database during the period of 2016-2024 related to risk management to develop a structured literature review. It was found that most of the studies were quantitative. Furthermore, risk management in previous research focused on company performance and corporate sustainability. Literature review studies are becoming increasingly important, as the connection to sustainability has recently become a compelling issue. The mapping results indicate that research related to risk management, sustainability, and corporate performance still has many limitations that can be addressed in future research. The originality of this article lies in its systematic review of 26 studies on the relationship between risk management, corporate governance, and CSR, identifying key research gaps and providing a comprehensive framework for future research on integrating sustainability and risk management practices.